2005
DOI: 10.1385/ep:16:1:041
|View full text |Cite
|
Sign up to set email alerts
|

Significance of an Insular Component in Follicular Thyroid Carcinoma with Distant Metastasis at Initial Presentation

Abstract: Risk factors for distant metastasis were studied in 82 patients with follicular thyroid carcinoma (FTC). Metastases to either the lung or bone existing at the time of presentation were confirmed by I-131 radio-iodine uptake in 10 patients. FTC with an insular component was found in eight patients. Univariate analysis of 14 possible risk factors showed 7 to be statistically significant: insular component, poorly differentiated carcinoma, trabecular component, serum thyroglobulin level before surgery, patient ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…A prominent spindle-cell component, or rhabdoid, oncocytic, or clear-cell phenotype, or signet-ring cells have been observed in rare FTC cases [75, 76]. Yamashita et al [77] suggested that the insular component in FTC was an independent risk factor for distant metastases to the lungs or bones. Heterogeneity of the tumour border is an unusual finding during FTC follow-up.…”
Section: Follicular Thyroid Carcinomamentioning
confidence: 99%
“…A prominent spindle-cell component, or rhabdoid, oncocytic, or clear-cell phenotype, or signet-ring cells have been observed in rare FTC cases [75, 76]. Yamashita et al [77] suggested that the insular component in FTC was an independent risk factor for distant metastases to the lungs or bones. Heterogeneity of the tumour border is an unusual finding during FTC follow-up.…”
Section: Follicular Thyroid Carcinomamentioning
confidence: 99%
“…Clinicopathological and morphological criteria like age, tumour size and presence of poorly differentiated areas in a well-differentiated thyroid carcinoma have been predominantly used to predict metastasis and overall survival 35 37. However, a considerable degree of interobserver variability exists for thyroid carcinomas, especially for thyroid neoplasms with follicular morphology.…”
Section: Micro-rnas and Thyroid Cancermentioning
confidence: 99%
“…32 The lack of E-cadherin expression is proposed as an independent prognostic factor for invasion by multivariate analysis. 33,34 Our case showed less than 80% of cells expressing membrane positivity for E-cadherin.…”
Section: -21mentioning
confidence: 63%